2023
DOI: 10.1111/1541-4337.13159
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of carbapenemase‐producing Enterobacteriaceae and associated resistance determinants through global food systems

Abstract: Antimicrobial agents are a critical component of modern healthcare systems, fulfilling a core function in patient care and improving individual patient outcomes and consequently overall public health. However, the efficacy of antimicrobial interventions is being consistently eroded by the emergence and dissemination of various antimicrobial resistance (AMR) mechanisms. One highly valued class of antimicrobial compounds is carbapenems, which retain efficacy in treating most multidrug‐resistant infections and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 176 publications
0
1
0
Order By: Relevance
“…The carbapenem resistance gene bla IMP is typically carried by plasmids but is occasionally reported to be carried on the chromosome [ 28 ]; for instance, Abe et al reported that bla IMP-6 was located on the chromosome in E. coli [ 29 ], and Miyazato et al reported that bla IMP-60 was located on the chromosome in Enterobacter asburiae [ 30 ]. In this study, we found a chromosomally integrated bla IMP-4 gene in K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…The carbapenem resistance gene bla IMP is typically carried by plasmids but is occasionally reported to be carried on the chromosome [ 28 ]; for instance, Abe et al reported that bla IMP-6 was located on the chromosome in E. coli [ 29 ], and Miyazato et al reported that bla IMP-60 was located on the chromosome in Enterobacter asburiae [ 30 ]. In this study, we found a chromosomally integrated bla IMP-4 gene in K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%